2012
DOI: 10.4236/ojvm.2012.22013
|View full text |Cite
|
Sign up to set email alerts
|

<i>Balantidium coli</i> in Pigs Regularly Slaughtered at Abattoirs of the Province of Messina: Hygienic Observations

Abstract: Balantidium coli is a zoonotic protozoan parasite, and pork is considered the major source of Balantidium infection in humans. Transmission is direct and commonly occurs through the ingestion of water and food, especially vegetables, contaminated with infectious cysts. Ingestion of meat contaminated, with faecal material during the evisceration process, can represent a potential risk of B. coli transmission. In order to determine the rate of B. coli infection in pigs regularly slaughtered at abattoirs in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
3
13
1
2
Order By: Relevance
“…The prevalence rate of Trichuris suis (6.43 %) was low and was similar to the reports from other tropical countries like Ghana (4.6 %) and Zimbabwe (4.2 %), by Permin et al, (1999) and Marufu et al, (2008), respectively. Ismail et al (2010) from Korea, Giarratana et al (2012) from Italy and Dey et al (2014) from Bangladesh reported higher prevalence rate of B. coli as 64.7 %, 36.66 % and 40 %, respectively which is contrary to the findings of the current study (4.5 %). Variation in prevalence of various species of GI parasites observed in the current study and other regions of the world, suggested that geographical location along with management practices including hygiene and deworming are the major determinants responsible.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence rate of Trichuris suis (6.43 %) was low and was similar to the reports from other tropical countries like Ghana (4.6 %) and Zimbabwe (4.2 %), by Permin et al, (1999) and Marufu et al, (2008), respectively. Ismail et al (2010) from Korea, Giarratana et al (2012) from Italy and Dey et al (2014) from Bangladesh reported higher prevalence rate of B. coli as 64.7 %, 36.66 % and 40 %, respectively which is contrary to the findings of the current study (4.5 %). Variation in prevalence of various species of GI parasites observed in the current study and other regions of the world, suggested that geographical location along with management practices including hygiene and deworming are the major determinants responsible.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the studies, prevalence and the intensity of infection varied between gender and age groups and in some cases opposite results were found between the studies, but probably the main factors affecting infection rates were the management practices at each farm and the veterinary care (Schuster and Ramirez-Avila, 2008). In general, facilities with cement floors, adequate cleaning protocols, and sewage disposal reduced the prevalence among pigs (Ismail et al, 2010;Giarratana et al, 2012;Weng et al, 2005;Yatswako et al, 2007; ).…”
Section: Reservoirsmentioning
confidence: 98%
“…Diversos reportes se帽alan que la prevalencia de la enfermedad en el cerdo es alta que puede variar entre 60% y 90% (Acha & Szyfres, 2005; ) y en algunos casos puede llegar al 100% (Verweij & Rune Stensvold, 2014) y constituyen el principal reservorio para la infecci贸n humana (Uysal et al, 2009;Publisher et al, 2014); en granjas tecnificadas y semitecnificadas de Cundinamarca, Colombia se encontr贸 el 42% de cerdos infectados con B. coli (Mendoza-G贸mez et al, 2015); en la provincia de Messina, Italia se report贸 86,06% de porcinos h铆bridos comerciales y s贸lo el 36,66% de cerdos de la raza negro siciliano estaban infectados por el par谩sito (Giarratana et al, 2012); as铆 como se report贸 el 93% de prevalencia del par谩sito en cerdos de Ranchi, Jahrkahnd, India (Bauri et al, 2012) y en Mymensingh, Bangladesh se report贸 una prevalencia de 34.62% (Rahman & Saha, 2015).…”
Section: Discussionunclassified